STEPnACT / Norazlin Mohamad … [et al.] - Mohamad, Norazlin; Mohan, Vikram; Alias, Nazhifah; Sarman, Nuraqilah (Division of Research and Industry Linkages, 2017)
Autism is a development disorder which can be recognized in early childhood with several problems such as socialization challenges, limited interest, repetitive utterance and movement as well as problem with imitation and mirroring. This is caused by hypo-responsiveness which is insufficient behavioural response toward sensory stimuli or low intensity in the present stimuli and can be overcome by practice and experience through playing. Earlier study conclude that these can be improved by the engagement of sharing enjoyment in a behaviour such as making eye contact, pointing and showing to an object, giving as well as commenting in the object throughout the playing activity among autistic children. Thus, to develop their social skills, communication and imagination, play therapy is one of the stepping stone to reach the goals. Existing ‘Twister’ game requires the player to perform complex gesture using both hands and legs on the mat which is considered to be hard for autism. Another existing innovation is based on the same concept which applies the high level of educational part using geographical illustration. In order to apply basic knowledge through the action of hands while stepping on the mat. an innovation is made. Our innovation, STEPnACT is a game that holds the concept of psycho-drama and mimicking in which daily basic activity, simple commands and easy communication are implemented that could increase their independence level without interrupting the enjoyment of playing (role-playing). The games consist of circle coloured pattern mat, colourful cards with image of simple activities and inflatable dice that is affordable, portable, suitable for 3 years old and above.The game also can be applied for developmental delay and normal children. The rules of the game requires the children to draw out the card and step on the circular colour on the mat followed by mimicking the action shown by the card.